Pemanfaatan Limbah Kulit Rambutan menjadi Teh Kulit Rambutan (Teh Kulitan) dalam Memberdayakan Kegiatan Wirausaha Ibu-Ibu Kajian Lembaga Sosial Al Hadad di Dusun Bedadung Wetan Desa Kaliwining Kecamatan Rambipuji - Siti Khayisatuzahro Nur (Mujtama': Jurnal Pengabdian Masyarakat, 2021)
The use of rambutan peel, which has only been used as trash around the community, has extraordinary properties. Its hair rind that contains xanthones as a strong antioxidant is needed by the body as a counterweight to prooxidants (reducing radicals, oxidizing radicals, carbon centered, UV rays, metals, etc.). The content of xanthones is also more than the xanthones contained in the mangosteen fruit. So it is very good if this rambutan peel/rind can be consumed by the public. Apart from being an antioxidant, the rambutan rind also contains various substances that are beneficial for health and beauty. However, the appearance of rambutan rind that is less attractive and its bitter taste is an obstacle for people to want to consume it. So in this service activity, we present how to process rambutan peel into one of the superior products and become herbal and functional products as well as efforts to reduce rambutan peel waste and increase the use value and selling value of the rambutan fruit. One of them is processing it into tea drinks. It is hoped that people can feel the benefits of rambutan rind without reducing the enjoyment of the taste when consuming it. And in its final goal, this training will develop entrepreneurial activities in the Bedadung Wetan community in entrepreneurship and innovating to create products that are unique to the people of Bedadung Wetan and have high economic value.